2017
DOI: 10.1111/hic3.12429
|View full text |Cite
|
Sign up to set email alerts
|

Reading Australian modernity: Unsettled settlers and cultures of mobility

Abstract: What did Australian modernity look like? Over the last two decades, Australia's entrenched reputation for ‘cultural belatedness’ has been displaced by the study of ‘colonial modernity’. No longer beholden to the idea that a singular modernity was disseminated from core to periphery, scholars now speak of many localised modernities that arose across colonial and provincial sites. According to this new ‘multiple modernities’ paradigm, Australia was home to its own home‐grown incarnation of modern life. But what … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 89 publications
(64 reference statements)
1
2
0
Order By: Relevance
“…Overall, these statistics point to a significant level of geographic mobility. This is in line with research that inter- and intra-national geographic mobility for elites was a hallmark of Australian modernity, and at the same time, a “product of privilege” (Rees, 2017, p. 3 of 13). As the next category showed, most of the women were also married.…”
Section: Demographic Aspects Of the Three Groups: Place Of Birthsupporting
confidence: 88%
“…Overall, these statistics point to a significant level of geographic mobility. This is in line with research that inter- and intra-national geographic mobility for elites was a hallmark of Australian modernity, and at the same time, a “product of privilege” (Rees, 2017, p. 3 of 13). As the next category showed, most of the women were also married.…”
Section: Demographic Aspects Of the Three Groups: Place Of Birthsupporting
confidence: 88%
“…Like other dominion women who underwent transformative departures in the post-war era, Denny, King and Kinane all thrilled in their international excursions, professionally and personally. They not only found a reprieve from the many complacencies of post-war Australian society, but they used their travels to embrace new mechanisms of modernity (Rees, 2017; Pesman, 1996: 218; Woollacott, 2001: 6). They immersed themselves in rapidly growing industrial communities and demonstrated a willingness to embrace new ideas, cultures and technologies.…”
Section: Network Of Supportmentioning
confidence: 99%
“…By the time the Australian colonies federated in 1901, the nation was home to 'intense cultures of both domestic and global mobility'. 34 For the transplanted white Britons who, until the late 1940s, composed 98 per cent of the non-indigenous population, long-distance journeys were embedded in daily life. During the interwar decades, tens of thousands visited London each year, while rates of automobile ownership were second only to the United States.…”
Section: Sojourning Across the Pacificmentioning
confidence: 99%